Stochastic Gradient Descent - Ketkar, Nikhil (Deep Learning with Python, 2017)
This chapter gives a broad overview and a historical context around the subject of deep learning. It also gives the reader a roadmap for navigating the book, the prerequisites, and further reading to dive deeper into the subject matter.